Connections in Teaching and Learning in Science and Mathematics Between upper High School Students and Higher Education - Narot, Pennee; Yuenyong, Chokchai; Phusithisak, Sutha (Kasetsart Journal of Social Sciences, 2014)
This is descriptive research with the data obtained by a survey method. The purposes of this study were to: (1) study the characteristics and pattern of Mathematics and Science teaching at the upper secondary school level, (2) study the characteristics and patterns of Mathematics and Science teaching in higher education, and (3) study the needs of university lecturers and professors regarding the contents in Mathematics and Science curricula and the desired characteristics of new entrants to the Mathematics and Science programs. Eight high schools in Khon Kaen province were randomly selected as well as Khon Kaen University. In order to obtain survey data, interviews and observation forms were used as research instruments. The data were analyzed using the statistics of mean, standard deviation, and percentage. It was found that the teaching approaches were partly useful for higher education. There was an enormous amount of content knowledge. The students felt that they were well trained in writing skills and self-directed learning as well as in analytical thinking skills. The university professors required students who were well equipped with knowledge, understanding, and scientific thinking skills; the new entrants also should have good attitude toward the subject, have the right concept, show ability in the subjective writing test and reasonable writing expression ability, and possess searching and recording skills. Importantly, school teachers have to be clear about both the pedagogical and content knowledge so they have in-depth knowledge to organize the learning instruction. These mathematics and science teachers should have the opportunity to participate in professional development continuously.